2018
DOI: 10.2215/cjn.13061117
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Rapid Correction of Severe Hyponatremia

Abstract: Background and objectives Rapid correction of severe hyponatremia can result in serious neurologic complications, including osmotic demyelination. Few data exist on incidence and risk factors of rapid correction or osmotic demyelination. Design, setting, participants, & measurements In a retrospective cohort of 1490 patients admitted with serum sodium ,120 mEq/L to seven hospitals in the Geisinger Health System from 2001 to 2017, we examined the incidence and risk factors of rapid correction and osmotic demyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 36 publications
3
73
2
4
Order By: Relevance
“…Effective serum osmolality is determined by serum sodium concentration. Hypotonic hyponatremia, if acute and severe, can lead to the entry of water into brain cells and ultimately, to cerebral edema [13,14]. The brain adapts to such a level of hypotonicity by losing intracellular solutes, principally potassium and organic solutes called osmolytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective serum osmolality is determined by serum sodium concentration. Hypotonic hyponatremia, if acute and severe, can lead to the entry of water into brain cells and ultimately, to cerebral edema [13,14]. The brain adapts to such a level of hypotonicity by losing intracellular solutes, principally potassium and organic solutes called osmolytes.…”
Section: Discussionmentioning
confidence: 99%
“…Overt rapid correction of hyponatremia can induce Osmotic Demyelination Syndrome (ODS) [13]. However, rapid correction in acute and severe hyponatremia does not induce ODS because the cerebral adaptation is still in its early stage [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hyponatremia is a potentially dangerous condition associated with the risk of brain edema . Another serious condition, central pontine myelinolysis, may occur when hyponatremia is treated rapidly . Minimizing the risk of hyponatremia may benefit the outcome after cardiac surgery, and preventing hyponatremia during CPB is most important.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise pathogenesis remains unclear, the most frequent trigger of myelinolysis in clinical practice is the rapid correction of chronic hyponatremia [ 2 ]. Osmotic demyelination has also been observed in other settings in the absence of rapid serum correction, such as hyperosmolar hyperglycemia, hyperammonemia, hypoxia, severe liver disease, and chronic alcoholism [ 4 ]. It is postulated that the brain adapts to chronically low levels of the intracellular osmolyte, and the subsequent iatrogenic hypertonic stress owing to rapid correction of hyponatremia causes the ions and water to quickly re-enter the intracellular space.…”
Section: Discussionmentioning
confidence: 99%